The role and regulation of intrarenal prostaglandin Eb2 in hypercalcemia. - Mangat, Harman. (University of Ottawa (Canada), 1998)
In chronic hypercalcemia, inhibition of medullary thick ascending limb (mTAL) NaCl reabsorption is mediated by elevated intrarenal prostaglandin E$\sb2$ (PGE$\sb2).$ The study presented here demonstrates that basolateral Na$\sp+$-K$\sp+$-ATPase activity is not affected by hypercalcemia. We also show that increased extracellular Ca$\sp{2+}$ and PGE$\sb2$ directly inhibit activity of the Na$\sp+$-K$\sp+$-2Cl$\sp{-}$ cotransporter. The mechanisms and source of elevated (PGE$\sb2$) in hypercalcemia are not understood. In rats fed dihydrotachysterol (DHT) to induce hypercalcemia, we measured the intrarenal expression of enzymes important in prostaglandin production, namely, cytosolic phospholipase A$\sb2$ (cPLA$\sb2),$ prostaglandin H synthase-1 (PGHS-1) and prostaglandin H synthase-2 (PGHS-2). The rate limiting step in prostaglandin synthesis in the PLA$\sb2$-mediated release of arachidonic acid from membrane phospholipids. Using Western blot analysis, we have shown expression of cPLA$\sb2$ in normal rat kidney tissue, with significant up-regulation after 3 days of hypercalcemia. PGHS-1 is expressed constitutively in almost all tissues including kidney and we found that PGHS-1 protein levels remained unchanged with hypercalcemia. Induction of PGHS-2, the other critical enzyme involved in prostaglandin synthesis, is generally associated with inflammation, mitogenesis and ovulation. PGHS-2 has also been shown to exist under unstimulated conditions in the kidney, and we have provided further support for this. In addition, we have demonstrated that PGHS-2 protein expression is significantly and maximally increased in hypercalcemic animals after 3 days of ingestion of DHT-containing diet, and displays a similar cellular pattern of distribution to cPLA$\sb2.$ However, unlike cPLA$\sb2$, after the initial stimulation on day 3, PGHS-2 protein levels in the inner and outer medulla return to baseline levels. Urinary PGE$\sb2$ excretion was significantly elevated in hypercalcemia rats after 5 days of DHT-containing diet. Angiotensin II has been reported to stimulate PGE$\sb2$ production in kidney tubular epithelial cells, mesangial cells and interstitial cells. We investigated the possibility that Ang II AT$\sb1$ receptor activation occurs in hypercalcemia, and mediates the increase in intrarenal cPLA$\sb2$ and PGHS-2 protein expression. Our data strongly support this hypothesis. Taken together, these data indicate that in chronic hypercalcemia, inhibition of NaCl reabsorption is not due to inhibition of the Na$\sp+$-K$\sp+$-ATPase pump. Both increased Ca$\sp{2+}\sb{\rm o}$ and PGE$\sb2$ inhibit the Na$\sp+$-K$\sp+$-2Cl$\sp-$ cotransporter, and we propose that these factors may be involved in the inhibition of NaCl transport in hypercalcemia. Furthermore, we demonstrate that hypercalcemia stimulates intrarenal cPLA$\sb2$ and PGHS-2 protein expression. Our data suggest that stimulation of cPLA$\sb2$ expression, through Ang II activation of the AT$\sb1$ receptor in the inner medulla, largely mediates increased PGE$\sb2$ excretion in hypercalcemic animals. (Abstract shortened by UMI.)
Keywords: Biology, Neuroscience.